The impact of transformational leadership on supplier relational stability: The moderating role of automation and globalization - Martin R. W. Hiebl; David I. Pielsticker (Business Strategy and the Environment, 2022)
Stable relationships with suppliers have been portrayed in the literature as having several economic and sustainability benefits. However, while a buyer firm's transformational leadership can be theorized to improve stable supplier relations, recent global business trends such as automation and globalization may endanger this stability. In this study, we therefore analyze the relationship between a buyer firm's transformational leadership and supplier relational stability and examine whether it is moderated by the buyer firm being affected by automation and globalization. We test our assumptions using data from a survey of German Mittelstand firms and confirm the moderating roles of automation and globalization. Our study therefore provides an updated and more nuanced understanding of how transformational leadership can affect supplier relational stability. Our findings also provide indications of how sustainable supplier relations can be achieved.
Keywords: 330; automation; globalization; stakeholder relations; supplier relational stability; sustainability; transformational leadership